2016
DOI: 10.1002/ejoc.201600543
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Multi‐Component Synthesis of Highly Functionalized Calix[4]arenes with Pronounced Binding Affinity toward β‐Lactoglobulin

Abstract: A facile and convenient approach for the synthesis of multi‐functionalized calix[4]arenes through multi‐component reactions is described. A series of five new calix[4]arene‐hexaamide derivatives were synthesized, and their structures were elucidated by means of spectroscopic data. The value of this method lies in its operational simplicity, mild reaction conditions, structural diversity of products, and good yields. Furthermore, fluorescence studies demonstrated considerable binding affinity of these new calix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A considerable attention has been paid to multi‐component reactions (MCRs) that possess a prominent position in modern organic synthesis and medicinal chemistry as the reactions are one‐pot procedures assembling three or more constituents and display high atom economy and high selectivity …”
Section: Introductionmentioning
confidence: 99%
“…A considerable attention has been paid to multi‐component reactions (MCRs) that possess a prominent position in modern organic synthesis and medicinal chemistry as the reactions are one‐pot procedures assembling three or more constituents and display high atom economy and high selectivity …”
Section: Introductionmentioning
confidence: 99%
“…The obtained results disclosed that any change in microenvironment of the tryptophan and tyrosine did not occur. 53 Also, the binding affinity of compound 3f toward some proteins has been investigated in a similar study (Scheme 7). Surprisingly, it was found that the binding affinity of 3f toward lysozyme (Lys) is signicantly higher than the others (Table 2).…”
Section: Arene Derivativesmentioning
confidence: 99%
“…Thus, the synthetic of highly functionalized calix[4]arene derivatives has become an active area of research. Recently, we have reported that highly functionalized calix[4]arenes have significant binding at proteins .…”
Section: Introductionmentioning
confidence: 99%